Hindering and enhancing factors to patient involvement in psychiatric hospital care : A focus group study - Varpula, Jaakko (fi=Turun yliopisto|en=University of Turku|, 2018)
Patient involvement is active participation between patients and healthcare professionals in decision making, planning, implementing, evaluating, training, and research. The importance of patient involvement has been identified nationally and internationally. Involving patients in their care improves satisfaction to and quality of care. Patient involvement can be hindered by patient induced, staff induced or organisation induced factors. To improve patient involvement, the experiences of the patients about hindering and enhancing factors to patient involvement in their psychiatric hospital care needs to be explored. The aim of this study was to explore what kind of hindering factors there are for patient involvement, and what ideas the patients have for enhancing patient involvement in their psychiatric hospital care Qualitative study design was used, where the data was collected with focus group interviews of patients (n=20) with experience of psychiatric hospital care. The data was analysed using qualitative content analysis. The results of this study indicated that the hindering factors to patient involvement in their psychiatric care are issues between the staff and the patients that stems from the relationship between the healthcare professionals and the patients. Issues in care delivery refer to hindering factors to patient involvement related to the care processes, practices and execution of care. Patient involvement can be enhanced by actions that the healthcare professionals perform and by staff holding attitude towards the patients which enhances patient involvement. Based on the study results, it is possible to enhance patient involvement in their psychiatric hospital care by taking into consideration the hindering and enhancing factors to patient involvement in the education and daily work of healthcare professionals, and in the planning of mental health services. Enhancing patient involvement is an important to the overall improvement of mental health services.